2022
DOI: 10.1136/jnnp-2022-329657
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to natalizumab throughout pregnancy: effectiveness and safety in an Italian cohort of women with multiple sclerosis

Abstract: ObjectiveAssessing the risk of clinical and radiological reactivation during pregnancy and post partum in women with multiple sclerosis (MS) treated with natalizumab (NTZ) throughout pregnancy (LONG_EXP) compared with women interrupting treatment before (NO_EXP) and within >−30 days and ≤90 days from conception (SHORT_EXP), and describing newborns’ outcomes.MethodsMaternal clinical and radiological outcomes and obstetric and fetal outcomes were retrospectively collected and compared among groups (NO_EXP, SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 26 publications
(40 reference statements)
4
16
2
Order By: Relevance
“…On the other hand, the presence of DMT escalation (in 11.7% and 41.5% of women with MS who were untreated or discontinued from their DMTs in the 12 months before conception, respectively) suggests relapse occurrence after delivery, or, at least, a perceived risk thereof (eg, MRI activity) 7 30–36. Overall, while we confirmed that a number of women with MS might not require DMT during pregnancy,8 in the case of active MS, safe medications should be considered to achieve disease control during pregnancy, at the time of delivery and afterwards, as recently shown in the case of natalizumab 37 38…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, the presence of DMT escalation (in 11.7% and 41.5% of women with MS who were untreated or discontinued from their DMTs in the 12 months before conception, respectively) suggests relapse occurrence after delivery, or, at least, a perceived risk thereof (eg, MRI activity) 7 30–36. Overall, while we confirmed that a number of women with MS might not require DMT during pregnancy,8 in the case of active MS, safe medications should be considered to achieve disease control during pregnancy, at the time of delivery and afterwards, as recently shown in the case of natalizumab 37 38…”
Section: Discussionsupporting
confidence: 60%
“…An important factor to consider is disease reactivation in response to natalizumab withdrawal [ 18 ] both prior or during pregnancy, which has serious implications leading to the accumulation of permanent irreversible disability [ 19 ]. More recent data add support to the approach of continuing natalizumab during pregnancy with early treatment postpartum, rather than cessation prior to or following conception, as this appears to be associated with lower clinical and radiological MS disease activity in the post-partum period [ 20 ].…”
Section: Safety Of Disease-modifying Therapies In Pregnancy and Breas...mentioning
confidence: 99%
“…In pregnancies exposed to natalizumab, no adverse fetal outcome emerged; however, there is the need to assess newborns’ risk of hematological alterations [ 35 , 37 ]. It is crucial to consider that the cessation of natalizumab may result in severe MS reactivation, highlighting the necessity of understanding the right time of drug discontinuation [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In pregnancies exposed to natalizumab, no adverse fetal outcome emerged; however, there is the need to assess newborns’ risk of hematological alterations [ 35 , 37 ]. It is crucial to consider that the cessation of natalizumab may result in severe MS reactivation, highlighting the necessity of understanding the right time of drug discontinuation [ 37 ]. To date, women with high-activity disease and a high risk of relapse are recommended to continue natalizumab until the beginning of the third trimester and then resume 8–12 weeks after delivery, possibly spacing out infusions during pregnancy [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation